Clinical evaluation of proximal contacts of Class II esthetic direct restorations - Prakki, Anuradha [UNESP]; Cilli, Renato [UNESP]; Saad, João Otávio Chalup; Rodrigues, José Roberto [UNESP] (My University, 2004)
Objective: This study evaluated the effectiveness of proximal contacts in Class II restorations using two types of matrix bands (steel and polyester) with two different restoration techniques (incremental and with prepolymerized particles). Method and materials: Eighty-eight Class II adjacent restorations using Prodigy resin composite were performed: 44 with the incremental technique (22 with steel matrix bands, 22 with polyester matrix bands) and 44 utilizing prepolymerized resin particles (22 steel matrix, 22 polyester matrix). The restorations were clinically evaluated at baseline and at 6, 12, and 18 months. Proximal contacts obtained immediately after restoration procedure in all restorations were satisfactory. Results: No statistically significant alterations were found in 18 months of evaluation. Conclusion: Regardless of the utilized resin composite, there were no differences in the amount of proximal contact variations with respect to tested techniques and matrices.
Keywords: Class II cavity; Clinical trial; Long-term study; Proximal contact; Resin composite; Restorative technique; polyester; resin; steel; clinical article; controlled study; dental care; dental caries; dental equipment; human; statistical significance; technique; Acid Etching, Dental; Composite Resins; Dental Cavity Preparation; Dental Polishing; Dental Restoration, Permanent; Dentin-Bonding Agents; Follow-Up Studies; Humans; Matrix Bands; Polyesters; Steel; Surface Properties